2000
DOI: 10.1037/0033-2909.126.2.309
|View full text |Cite
|
Sign up to set email alerts
|

The neighborhoods they live in: The effects of neighborhood residence on child and adolescent outcomes.

Abstract: This article provides a comprehensive review of research on the effects of neighborhood residence on child and adolescent well-being. The first section reviews key methodological issues. The following section considers links between neighborhood characteristics and child outcomes and suggests the importance of high socioeconomic status (SES) for achievement and low SES and residential instability for behavioral/emotional outcomes. The third section identifies 3 pathways (institutional resources, relationships,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

126
2,531
19
60

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,849 publications
(2,736 citation statements)
references
References 128 publications
(254 reference statements)
126
2,531
19
60
Order By: Relevance
“…Neighborhoods constitute a key determinant of racial and socioeconomic disparities in health, as they shape individual opportunities and expose residents to multiple risks and resources over the lifecourse (Leventhal & Brooks-Gunn, 2000;Sampson, 2003). A growing literature has shown that the neighborhood environment is associated with reproductive health outcomes, and recent studies suggest that neighborhood poverty aggravates the increasing risk of low birthweight with maternal age (J. W. Collins, Simon, Jackson, & Drolet, 2006;Geronimus, 1992;Rauh, Andrews, & Garfinkel, 2001).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Neighborhoods constitute a key determinant of racial and socioeconomic disparities in health, as they shape individual opportunities and expose residents to multiple risks and resources over the lifecourse (Leventhal & Brooks-Gunn, 2000;Sampson, 2003). A growing literature has shown that the neighborhood environment is associated with reproductive health outcomes, and recent studies suggest that neighborhood poverty aggravates the increasing risk of low birthweight with maternal age (J. W. Collins, Simon, Jackson, & Drolet, 2006;Geronimus, 1992;Rauh, Andrews, & Garfinkel, 2001).…”
Section: Nih Public Accessmentioning
confidence: 99%
“…[8][9][10] This results in neighborhoods wherein a wide array of illegal behavior, including drug use, may be reinforced. 11,12 Neighborhood disorganization can also lead to a lack of trust and solidarity among residents, making it unlikely that neighbors will intervene on behalf of the community. 13 In some instances where neighborhood disorder becomes severe, "the law of the streets" may prevail over the will of the residents.…”
Section: Introductionmentioning
confidence: 99%
“…16 Research has established many negative outcomes associated with such disadvantaged neighborhood conditions. 12,15,17,18 Place-based interventions have the potential to influence a Bculture of health^that supports healthy lifestyles at home, work, play, and in the places in-between, 2 and that impacts population-scale health and safety. Moreover, the influence of placebased changes often occur without asking would-be beneficiaries to change their habits, adhere to treatment regimens, or remember classroom training they may have once received.…”
mentioning
confidence: 99%